Subcutaneous injection of infliximab CT‐P13 results in stable drug levels within 14‐day treatment cycle in Crohn's disease. Issue 1 (28th February 2022) - Roblin, Xavier; Veyrard, Pauline; Bastide, Laetitia; Berger, Anne E.; Barrau, Mathilde; Paucelle, Anne‐Sophie; Waeckel, Louis; Kwiatek, Sany; Flourie, Bernard; Nancey, Stephane; Paul, Stéphane
Summary: The new subcutaneous (sc) formulation of the infliximab (IFX) biosimilar CT‐P13 results in homogeneous serum trough concentrations of IFX at steady state. The present study aimed to investigate in Crohn's disease (CD) patients the intra‐individual variations of IFX drug levels at multiple time‐points during 2 consecutive cycles of maintenance therapy with CT‐P13 sc. Patients and Methods: CD patients in clinico‐biological remission under maintenance therapy with intravenous (iv) IFX/CT‐P13 were switched to CT‐P13 sc 8 weeks (W) after the last infusion. They were treated with CT‐P13 sc, 120 mg every 2 W. Assessments were performed from 8 W after starting CT‐P13 sc and patients had to attend 6 visits on 2 consecutive cycles of treatment (cycles A and B). Visits were scheduled on days 4–6 (visit 1), days 7–9 (visit 2) and day 14 (visit 3) of each cycle, where days 1 and 14 were the days of sc injection of CT‐P13. At each visit, peripheral blood was collected to measure serum IFX levels and anti‐drug antibodies. Results: Twenty patients underwent 120 evaluations. Large intra‐individual variations of serum drug levels of IFX were observed. When pooling the 120 evaluations, the mean drug level was 11.3 ± 4.9 μg/ml, and the median drug level was 10.9 μg/ml (IQR 7.5–15.5). During each cycle, the median drug levels were similar between visits 1 and 2 as well as between visits 1 and 3 and between visits 2 and 3. In cycle A, median drug levels were 11.1 μg/ml (7.8–14.5), 12.0 μg/ml (7.2–16.1) and 11.0 μg/ml (7.5–15.1) at V1, V2 and V3, respectively. Similar results were obtained in cycle B, where median drug levels were 11.6 μg/ml (7.9–14.9), 11.4 μg/ml (8.1–15.2) and 10.9 μg/ml (7.9–15.6) at V1, V2 and V3, respectively. In univariate analysis, we failed to identify factors predictive of low drug levels. Conclusions: IFX drug levels are quite stable within 14‐day treatment cycle, without trough levels in CD patients in remission during the maintenance therapy with CT‐P13 sc. In patients with inactive CD under maintenance therapy with CT‐P13 sc, therapeutic drug monitoring of IFX can be performed at any time between two CT‐P13 sc injections. Abstract : CPT‐13 drug levels are stable within 14 days treatment cycle but also between cycles.